Muscle architecture and neuromuscular changes after high-resistance circuit training in hypoxia - Ramos-Campo, D. J.; Martínez-Guardado, I.; Rubio-Arias, J. A.; Freitas, T. T.; Othalawa, S.; Andreu, L.; Timón, R.; Alcaraz, P. E. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to analyze the effect of 8 weeks of high-resistance circuit (HRC) training in hypoxia on muscle architecture, strength, and neuromuscular variables. Twenty-eight resistance-trained subjects were assigned to a hypoxia (FiO2 = 15%; HG: n = 15; age: 24.6 ± 6.8 years; height: 177.4 ± 5.9 cm; and mass: 74.9 ± 11.5 kg) or normoxia group (FiO2 = 20.9%; NG: n = 13; age: 23.2 ± 5.2 years; height: 173.4 ± 6.2 cm; and mass: 69.4 ± 7.4 kg). Each training session consisted of 2 blocks of 3 exercises (block 1: bench press, leg extension, and front lat pulldown; block 2: deadlift, elbow flexion, and ankle extension). Each exercise was performed with a 6 repetition maximum load. Subjects exercised twice weekly and, before and after the training program, vastus lateralis muscle thickness and pennation angle, knee extensors electromyographic activity, maximum voluntary contraction (MVC), and rate of force development (RFD) and H-Reflex (Hmax), M-wave of the soleus muscle were assessed. Both training groups showed similar improvements in muscle thickness (effect size [ES] = HG: 0.23; NG: 0.41), pennation angle (ES = HG: 0.86; NG: 0.15), MVC (ES HG: 0.63; NG: 0.61), Hmax (ES = HG: 0.96; NG: 0.40), RFD at 200 milliseconds (ES = HG: 0.31; NG: 0.61) and peak RFD (ES = HG: 0.21; NG: 0.66). No significant between-group differences were found. In conclusion, similar morphological and neuromuscular adaptations can be achieved after 8 weeks of HRC training under hypoxic or normoxic conditions.